(untitled) (Politeja, 2015)
The European Parliament’s Role in Shaping the European Union’s Energy Security Participation of the European Parliament in the process of energy sector communitarization and providing assurance of Community energy security is enormous due to its position and its legitimacy in European institutions structure. European Parliament – through its participation in the development of energy acquis communautaire, under the ordinary legislative procedure – is a full‑fledged entity responsible for the shape of EU’s legal order, and the views of MPs interact indirectly on EU law and policies final version. Using indirect legislative initiative, the European Parliament has become also an active creator providing the mandate of EC political initiatives. Consequently, the European Parliament has played an important role at the supranational level in the energy sector communitarization, often acting as a political forum facilitating building of compromises, necessary to deepen the EU’s energy policy. It also actively participates in the development of EU energy and climate policy.